Trichoderma e bradyrhizobium no desenvolvimento e produtividade da soja - Cadore, Luana da Silva (2018)
Soy is a very important crop and for success in cultivation, many factors are critical and help increase productivity. One of these factors is the seed treatment, since it aims to ensure the protection of seeds in the soil. Among the products used for the treatment of seeds are bio-products based on fungi of the genus Trichoderma spp. that act in the promotion of growth of plants and bacteria of the genus Bradyrhizobium japonicum that help in the biological fixation of nitrogen. Thus, the objective of this work was to evaluate the isolated and associated use of bioproducts based on Trichoderma spp. and Bradyrhizobium japonicum on the mitotic index of soybean roots, on soybean development and yield. The treatments used were: Control (absence of trichoderma and Bradyrhizobium japonicum), Ecotrich®, Trichodel®, Bionutri® liquid, Bionutri® peat, Ecotrich® associated with Bionutri® liquid, Ecotrich® associated with Bionutri® peat, Trichodel® associated with Bionutri® and Trichodel® associated with Bionutri® peat.Was evaluated: germination; emergency; length of aerial part; leaf area; root length; fresh and dry matter of shoot and root; surface area, root diameter and volume; first pod insertion; weight of pods; weight of a thousand grains and yield of grains. From the data obtained, it is concluded that the use of commercial bioproducts based on Trichoderma spp. and Bradyrhizobium japonicum in an associated or isolated manner provide better initial development for soybean cultivation as well as increase in final yield of the crop.